2003
DOI: 10.1080/00905990307129
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Social Distance in Kyrgyzstan: Evidence from a Nationwide Opinion Survey1

Abstract: Unlike in some other former Soviet republics, when Kyrgyzstan achieved independence in 1991 its government granted citizenship to all residents, regardless of ethnicity or language. The government hoped this would help to quell incipient ethnic tensions in the country before they got out of hand. It was argued that, in a constantly changing ethnic landscape, citizens' identification with the country above all other considerations, including ethnicity and religion, would introduce a degree of stability—a common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…After an early post‐Soviet plunge, Kyrgyzstan's economy saw a rapid recovery from the beginning of this century, but with a gross national income (GNI) per capita of US$ 1,220, it remains one of the poorest countries in Central Asia (World Bank, 2018). Like many former Soviet republics, Kyrgyzstan is a multi‐ethnic nation, with a complex mix of ethno‐cultural and regional identities, cleavages and inequalities that are strongly imprinted on the nation's socio‐political and economic fabric (Anderson and Pomfret, 2000; Elebayeva et al., 2000; Esenaliev and Steiner, 2014; Faranda and Nolle, 2003, 2011). In addition to Kyrgyz, the titular majority, its population includes Uzbeks, another indigenous Turkic‐speaking ethnic group; a sizeable mix of European‐origin, mainly Russian‐speaking groups, primarily ethnic Russians, but also Ukrainians, Byelorussians, Germans (from Russia's Volga region) and others who moved to Kyrgyzstan, voluntarily or forcibly, during the Soviet era; and several other smaller native and non‐native groups.…”
Section: Contextmentioning
confidence: 99%
“…After an early post‐Soviet plunge, Kyrgyzstan's economy saw a rapid recovery from the beginning of this century, but with a gross national income (GNI) per capita of US$ 1,220, it remains one of the poorest countries in Central Asia (World Bank, 2018). Like many former Soviet republics, Kyrgyzstan is a multi‐ethnic nation, with a complex mix of ethno‐cultural and regional identities, cleavages and inequalities that are strongly imprinted on the nation's socio‐political and economic fabric (Anderson and Pomfret, 2000; Elebayeva et al., 2000; Esenaliev and Steiner, 2014; Faranda and Nolle, 2003, 2011). In addition to Kyrgyz, the titular majority, its population includes Uzbeks, another indigenous Turkic‐speaking ethnic group; a sizeable mix of European‐origin, mainly Russian‐speaking groups, primarily ethnic Russians, but also Ukrainians, Byelorussians, Germans (from Russia's Volga region) and others who moved to Kyrgyzstan, voluntarily or forcibly, during the Soviet era; and several other smaller native and non‐native groups.…”
Section: Contextmentioning
confidence: 99%
“…The north–south divide has deep historical roots and its political, social, and economic implications have been widely acknowledged in the literature (e.g. Faranda and Nolle, 2003; Ryabkov, 2008). Thus, northern Kyrgyz had greater exposure to Russian culture and language during the Soviet rule and as a result, are, in general, more ‘Russified’ in cultural and linguistic terms than their southern counterparts.…”
Section: Contextmentioning
confidence: 99%
“…Nevertheless, there have been a few noteworthy attempts to fill various gaps. For example, Faranda and Nolle (), working with a national probability sample of Kyrgyzstani adults surveyed in 2001, built a Muslim religiosity scale analyzing responses to four questions about praying five times a day, observing the fast during Ramadan, hoping to make a pilgrimage to Mecca, and attending a place of worship more than once a year. Though they correctly accounted for the fact that worship attendance as a measure of religiosity functioned differently for women and men, they observed that their measurement of worship attendance may have confounded mazar attendance with mosque attendance.…”
Section: Introductionmentioning
confidence: 99%